The Oxford handbook of the economics of central banking - Mayes, David G.; Siklos, Pierre L., 1955-; Sturm, Jan-Egbert, 1969- (New York, NY : Oxford University Press, 2019)
The Oxford Handbook of the Economics of Central Banking covers a wide range of central bank topics, including governance, independence, balance-sheet and crisis management, and the challenges in macroeconomic modeling. The book is intended as an up-to-date reference for the current and potential challenges faced by central banks in the conduct of monetary policy and in the search for the maintenance of financial system stability. The approach involves a wide variety of views about the past and present behavior and performance of central banks around the world, with the aim of providing a state-of-the-art perspective on the likely future challenges to be faced by this critical institution. Clearly, one of the motivations for the book is the great financial crisis of 2007-2009.
Central Banking's 'Long March' Over the Decades / David G. Mayes, Pierre L. Siklos, Jan-Egbert Sturm -- Transparency of Monetary Policy in the Post-Crisis World / Nergiz Dincer, Barry Eichengreen, Petra Geraats -- Real Estate, Construction, Money, Credit and Finance / Peter Sinclair -- Inside the Bank Box: Evidence on Interest Rate Pass-Through and Monetary Policy Transmission / Leonardo Gambacorta, Paul Mizen -- Term Premium Variability and Monetary Policy / Timothy S. Fuerst, Ronald Mau -- Open Market Operations / Jan Toporowski -- Central Banking and Prudential Regulation: How The Wheel Turns / Kevin Davis -- The Changing Consensus on the Central Bank's Role in Financial Stability and Supervision / Michael W. Taylor, Douglas W. Arner, Evan C. Gibson -- Central Banks and the New Regulatory Regime for Banks / David T. Llewellyn -- Macroprudential Regulation of Banks and Financial Institutions / Gerald P. Dwyer -- Central Banking and Crisis Management from the Perspective of Austrian Business Cycle Theory / Gunther Schnabl -- Monetary Policy Committees and Voting Behaviour / Sylvester Eijffinger, Ronald Mahieu, Louis Raes -- The Changing Role of the Central Bank in Crisis Avoidance and Management / David G. Mayes -- Managing Macrofinancial Crises: The Role of the Central Bank / Patrick Honohan, Domenico Lombardi, Samantha St. Amand -- Macro-Modelling, Default and Money / Charles Goodhart, Nikolaos Romanidis, Dimitrios P. Tsomocos, Martin Shubik -- Model Uncertainty in Macro Economics: On the Implications of Financial Frictions / Michael Binder, Philipp Lieberknecht, Jorge Quintana, Volker Wieland -- What Has Publishing Inflation Forecasts Accomplished? : Central Banks and Their Competitors / Pierre L. Siklos -- Peaks and Troughs: Economics and Political Economy of Central Bank Independence Cycles / Donato Masciandaro, Davide Romelli -- The Governance of Central Banks: With Some Examples from
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on March 11, 2019).
Keywords: Banks and banking, Central; Monetary policy